NetCAPE enabling seamless IMS service delivery across heterogeneous mobile networks. - Udugama, Asanga (IEEE Communications magazine)
An evolving wireless world is constantly providing users with a wider set of access technologies to choose from, each with different capabilities and properties. In this world, IMS as defined by 3GPP provides an enabling, standardized multimedia architecture that is access independent, hence, providing service convergence. This trend is accompanied by an increasing number of multimode terminals so that inter-access- system-service continuity gains relevance. This article presents the architectural framework of NetCAPE (networking context aware policy environment), which addresses the optimization of mobility management in such a heterogeneous environment while interacting with IMS applications to enable seamless service delivery across heterogeneous mobile networks; even as the mobility offered by the underlying network remains transparent to IMS applications. Although the focus is on 3GPP-based mobile networks, the framework also incorporates wired access technologies, hence, taking a further step toward fixed mobile convergence (FMC). First results are presented highlighting the improvements gained by applying NetCAPE concepts.